Peran Pemerintahan Desa Ulumahuam Dalam Upaya Pengembangan Ekonomi Masyarakat - Yungki Akbar; Yani Lubis (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This research is based on the views of the life of the Ulumahuam Village community, Silangkitang District who are able to adjust the economic conditions for the transformation of the methods of most of the livelihoods towards modernization, digitalization and tactics. However, behind the ability of the local community to deal with this, there is an important role for the Ulumahuam Village Government which previously provided education in various ways such as holding training/workshops, seminars, community outreach, environmental empowerment, distribution of community economic power to local MSME development. This research uses descriptive qualitative analysis research by making several information providers from internal & external Ulumahuam Village Government. The role of the Ulumahuam Village Government is very helpful for the growth and development of the community's economy as it is currently felt, this is frontal because the community can adjust the conditions of the economic cycle after changes in domestic/domestic economic patterns. The government is also sensitive to the attitude of public concern in many ways, including infrastructure that also supports the wheels of the economy and facilitates the needs of arts and sports, especially for local youth. However, there is still homework that needs to be improved and completed, namely rebuilding religious activities for local youths such as the Youth Mosque, one of which has long stopped. Keyword : Peran Pemerintahan Desa, Upaya Pembangunan Ekonomi, Masyarakat